Le microbiote du lait de chamelle d'origine marocaine, une source de nouvelles bactéries lactiques - Kadri Zaina (Université Sidi Mohamed Ben Abdellah, Faculté des Sciences et Techniques - Saïs -, Fès, 2016)
Raw camel milk plays an important role in the daily diet of pastoralists in dry area of African countries like Morocco. The aim of the present study was to identify lactic acid bacteria (LAB) isolated from camel milk produced in Morocco, using molecular meth-ods. Twelve samples were collected from eight different locations in Morocco. A total of one hundred twenty nine LAB isolates were obtained from nine of the analyzed sam-ples and were subjected to a stepwise identification approach combining (GTG)5-PCR fingerprinting and 16S rRNA gene sequence analysis. LAB associated with camel milk were identified as Leuconostoc (Leuc.) mesenteroides subsp. mesenteroides (41.1%), Lactococcus (L.) lactis subsp. lactis (31.8%), Leuc. pseudomesenteroides (6.9%), L. lactis subsp. cremoris (6.2%), Leuc. citreum (5.4%), Leuc. mesenteroides subsp. dex-tranicum (2.3%), Enterococcus (E.) faecium (1.6%), E. durans (0.8%) and L. raffi-nolactis (0.8%); in addition, four isolates (3.1%) represented four new Streptococcus species which were classified as Streptococcus (S.) moroccensis sp. nov., S. rifensis sp. nov., S. cameli sp. nov., and S. tangierensis sp. nov., (see chapters 5.2 and 5.3). Leuc. mesenteroides subsp. mesenteroides and L. lactis subsp. lactis were common LAB iso-lated from most of analyzed samples.
Keywords: Biologie Moléculaire; Génétique; Raw camel milk; Lactic acid bacteria; Stepwise identification approach; (GTG)5-PCR fingerprinting; 16S rRNA gene sequence analysis